Morphological and molecular differences between the Amphiamerican populations of Antillesoma (Sipuncula: Antillesomatidae), with the description of a new species - Silva-Morales, Itzahí; López-Aquino, Mónica J.; Islas-Villanueva, Valentina; Ruiz-Escobar, Fernando; Bastida-Zavala, J. Rolando (Revista de Biología Tropical, 2019)
Introduction: The sipunculans are a group of marine invertebrates that have been little studied in the tropical eastern Pacific (TEP). Antillesoma antillarum is a species belonging to the monospecific family Antillesomatidae, considered widely distributed in tropical and subtropical localities across the globe. Objective: The main objective of this work was to examine the morphological and molecular differences between specimens from both coasts of tropical America to clarify the taxonomy of this species. Methods: We examined the morphology with material from the Mexican Caribbean and southern Mexican Pacific. To perform molecular analyses, two sequences of the COI molecular marker were obtained from specimens collected in Panteón Beach, Oaxaca, southern Mexican Pacific, and compared with four sequences identified as A. antillarum in GenBank, all of them from different localities. A phylogenetic reconstruction was performed with the maximum likelihood method and genetic distances were calculated with the Kimura 2P model and compared to reference values. Results: The phylogenetic analysis revealed three different lineages of Antillesoma that are well supported by bootstrap values: Antillesoma antillarum sensu stricto from the Caribbean Sea and Florida; a sister group to the one represented by our samples from the Mexican Pacific; and a third group from Thailand. Conclusion: Based on morphological traits and molecular data, Antillesoma mexicanum sp. nov. is described from the Mexican Pacific, differing from A. antillarum in the trunk papillae, color patterns and, additionally, the specimens from the Caribbean attain significantly bigger trunk sizes than the ones Pacific.